Conditions for parents' participation in the care of their child in neonatal intensive care - a field study - Berg Marie; Hellström Anna-Lena; Wigert Helena (BMC, 2008)
Abstract Background To promote participation by parents in the care of their child in neonatal intensive care units (NICU), health professionals need better understanding of what facilitates and what obstructs participation. The aim was to elucidate conditions for parents' participation in the care of their child in NICUs. Methods A field study with a hermeneutic lifeworld approach was used and data were collected at two NICUs through participative observations and interviews with representatives of management, staff and parents. Results The results point to a number of contradictions in the way parents were offered the opportunity to participate in neonatal intensive care. Management and staff both had good ambitions to develop ideal care that promoted parent participation. However, the care including the conditions for parental participation was driven by the terms of the staff, routines focusing on the medical-technical care and environment, and budgetary constraints. Conclusion The result shows that tangible strategies need to be developed in NICUs aimed at optimising conditions for parents to be present and involved in the care of their child.